Coronashaming: interpersonal affect worsening in contexts of COVID-19 rule violations. Issue 1 (2nd January 2022) - López-Pérez, Belén; Hanoch, Yaniv; Gummerum, Michaela
ABSTRACT : Experiencing empathy for others has been linked to worsening others' feelings against their wishes. These paternalistic empathic goals have been theorised to happen at the dyad level when an agent aims to worsen a target's emotional state. They may also operate at a broader level when agents are third-party observers of COVID-19 lockdown rule violations. In these instances, agents can impact transgressors' affect engaging in Coronashaming . In three studies, we measured British people's ( N total  = 767) vulnerability (Study 1), age (Studies 2 and 3), and empathy towards COVID-19 victims and presented them with different scenarios depicting a breach of lockdown rules to assess the emotions participants wanted to inflict in transgressor, the strategies used, and whether they wanted stricter rules to be enforced. Results confirmed shame as the emotion preferred to induce in violators, with this preference linked to higher use of engagement strategies (i.e. to make transgressors understand what they did wrong). Finally, empathy was positively linked to higher affect worsening and wanting stricter rules to be enforced. This suggests that empathy towards potential victims of COVID-19 rules violations can motivate people to worsen the feelings of transgressors.